Tinjauan kaidah Fiqhiyyah dalam Pencatatan Perwakafan di Indonesia - Adang Muhamad Nasrulloh (Isti`dal : Jurnal Studi Hukum Islam, 2023)
The practice of waqf in Indonesia is often found in the community. However, it is undeniable that waqf land disputes often occur, as a result, waqf objects are taken back by their heirs. One of the factors taken is the lack of legality in the form of an authentic deed of waqf objects. Through this article, the researcher tries to examine the regulations regarding the recording of waqf with the fiqhiyyah rule approach. The method used is a qualitative method with a literature study approach. The results of this study indicate that a series of laws and regulations that have been set by the government are in line with the rules that have been set by previous scholars, even the recording of waqf nowadays can be categorized as mandatory.